2022
DOI: 10.3390/jpm12071111
|View full text |Cite
|
Sign up to set email alerts
|

Modeling a Novel Variant of Glycogenosis IXa Using a Clonal Inducible Reprogramming System to Generate “Diseased” Hepatocytes for Accurate Diagnosis

Abstract: The diagnosis of inherited metabolic disorders is a long and tedious process. The matching of clinical data with a genomic variant in a specific metabolic pathway is an essential step, but the link between a genome and the clinical data is normally difficult, primarily for new missense variants or alterations in intron sequences. Notwithstanding, elucidation of the pathogenicity of a specific variant might be critical for an accurate diagnosis. In this study, we described a novel intronic variant c.2597 + 5G &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Complementary DNA analysis in the proband revealed the skipping of exon 21, indicating that the deletion introduced a premature stop codon, p.Pro789Serfs*21 (Figure 1C). We speculate that this variant would trigger nonsense‐mediated mRNA decay, based on a previous study using hepatocyte‐like cells generated from the dermal fibroblast cell line of a male patient with PHKA2 c.2597+5G>T, showing (i) the variant resulted in an aberrant splicing of PHKA2 and the incorporation of a 27 bp into exon 23 with the immediate presence of a stop codon, (ii) PHKA2 mRNA was down‐regulated 7‐ to 11‐fold, and (iii) mutant PHKA2 protein expression was absent 3 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Complementary DNA analysis in the proband revealed the skipping of exon 21, indicating that the deletion introduced a premature stop codon, p.Pro789Serfs*21 (Figure 1C). We speculate that this variant would trigger nonsense‐mediated mRNA decay, based on a previous study using hepatocyte‐like cells generated from the dermal fibroblast cell line of a male patient with PHKA2 c.2597+5G>T, showing (i) the variant resulted in an aberrant splicing of PHKA2 and the incorporation of a 27 bp into exon 23 with the immediate presence of a stop codon, (ii) PHKA2 mRNA was down‐regulated 7‐ to 11‐fold, and (iii) mutant PHKA2 protein expression was absent 3 …”
Section: Figurementioning
confidence: 99%
“…We speculate that this variant would trigger nonsense-mediated mRNA decay, based on a previous study using hepatocyte-like cells generated from the dermal fibroblast cell line of a male patient with PHKA2 c.2597+5G>T, showing (i) the variant resulted in an aberrant splicing of PHKA2 and the incorporation of a 27 bp into exon 23 with the immediate presence of a stop codon, (ii) PHKA2 mRNA was down-regulated 7-to 11-fold, and (iii) mutant PHKA2 protein expression was absent. 3 A previous study suggested that Alu-mediated recombination causes a 10-kb deletion of several exons in PHKA2. 4 To our knowledge, other mechanisms causing PHKA2 microdeletions are unknown.…”
mentioning
confidence: 98%
“…Organ ini berperan aktif dalam metabolisme seperti mengeluarkan empedu yang memecah lemak dalam usus kecil selama pencernaan, menyimpan dan melepaskan glukosa, serta mensintesis berbagai jenis protein (Zaefarian et al, 2019). Selain itu, hati juga mengubah amonia berbahaya menjadi urea, mengolah hemoglobin, membersihkan bilirubin, melawan infeksi, dan mendetoksifikasi obatobatan dan bahan kimia beracun lainnya (Garcia-Llorens et al, 2022). Namun, hati juga dapat dengan mudah mengalami kerusakan karena penumpukan metabolit yang tidak diinginkan atau zat beracun (Palawe et al, 2021).…”
Section: Pendahuluanunclassified
“…This is usually accomplished by ectopic expression of key liver enriched transcription factors, most frequently HNF4A and either FOXA1, FOXA2 or FOXA3. We selected expression of HNF4A, FOXA3 together with HNF1A based on previous studies [8] and the robustness of this combination in our own laboratory [7,[9][10][11]. However, since differentiation stops cell growth, generation of large quantities of HLC requires an additional step to override the proliferation arrest induced by the expression of these factors.…”
Section: Introductionmentioning
confidence: 99%